Factores que afectan la eficiencia de la inseminación artificial en el programa de mejoramiento genético sostenible de bovinos de leche en la provincia de Cotopaxi en el periodo de abril - Agosto del 2023. - Landeta Martínez, Ricardo Francisco (2023)
The present study aimed to identify the factors that affect the success of Artificial Insemination (AI) in the sustainable genetic improvement program of dairy cattle. The population consisted of small dairy cattle producers in a parish, and a sample of 44 farmers who used AI in their activities was selected. Through surveys and statistical analysis, various environmental, management, and AI technique factors that could influence the procedure's effectiveness were evaluated. The results revealed that AI efficiency was significantly related to detecting the return of estrus at 21 days, the parish where AI was performed, and the presence of vaginal discharge in cows. Additionally, the breed of the bull used also influenced AI efficiency. However, factors such as age, weight, body condition, and AI duration did not show significant associations with its effectiveness. Based on these findings, an AI protocol was developed aiming to improve the procedure's efficacy in dairy cattle, considering the identified factors as determinants in the reproductive process. This protocol includes the careful selection of bulls with high reproductive efficiency, estrus synchronization, pre-AI examination, and post-AI monitoring to ensure a precise evaluation of cow health. Furthermore, the importance of staff training and consideration of environmental factors are highlighted to maximize conception rates.